Sustainable Agriculture in Subang: Integrating Local Wisdom, Sharia Principles, and Agribusiness Innovation - Nurlailiyah Aidatus Sholihah; Fikry Ramadhan Suhendar; Faisal Bin Husen Ismail; Muhammad Masruri (UIN Sunan Gunung Djati Bandung, 2026)
This research examines the influence of local cultural knowledge, Islamic (Sharia-based) values, and agribusiness innovations on the development of sustainable agricultural practices in Subang, West Java, Indonesia. Employing a qualitative document analysis approach, the study explores how indigenous traditions such as the Mapag Sri ritual and collective labor systems (gotong royong) play a significant role in maintaining ecological sustainability and social cohesion within farming communities. These local practices are reinforced by Islamic ethical principles, including ʿadl (justice), barakah (divine blessing), and zakat al-zurʿ (agricultural almsgiving), which guide moral responsibility in agricultural production, distribution, and resource management. In parallel, the adoption of agribusiness innovations particularly digital farming technologies, cooperative-based management, and improved market access enhances productivity, efficiency, and farmers’ economic resilience. The findings demonstrate that sustainability in Subang is not the result of isolated interventions, but rather emerges from a coherent system in which cultural traditions, religious ethics, and modern technological practices mutually reinforce one another. This integrated framework strengthens environmental stewardship, promotes ethical governance, and supports long-term socio-economic resilience in rural communities. The study contributes a context-sensitive model of sustainable agriculture that successfully bridges tradition and modernity within a Muslim-majority setting. It offers valuable insights for policymakers, development practitioners, and scholars concerned with rural development, Islamic economics, and sustainable livelihoods. Furthermore, the model proposed in this research may serve as a transferable framework for other agricultural regions undergoing similar socio-cultural and economic transformations.